Properties of New Flows Indicate that Martian Gullies Form via CO2 Frost‐Fluidization Processes - Colin M. Dundas; Susan J. Conway; Kelly Pasquon; Axel Noblet; Lonneke Roelofs (Geophysical Research Letters)
Abstract Martian gully landforms are widely seen as evidence of liquid water, often attributed to snowmelt during high‐obliquity periods within the last few million years. However, widespread present‐day flows within existing gullies are caused by CO2 frost, presenting an alternative formation mechanism. Entrained frost vapourizes to fluidize flows, allowing them to behave similarly to wet debris flows on Earth. The slopes where present‐day flows erode and deposit provide insights into the landforms that many such flows could create. The shallowest slopes eroded by the flows are similar to slopes at existing channel mouths, and the most mobile flows reach final slopes similar to the outer reaches of existing gully aprons. This is consistent with formation of gullies entirely by CO2 frost‐driven flows, assuming their intensity and frequency varies in space and time. Geologically recent snowmelt cannot be ruled out, but is not required to explain the observed gully morphology.